Penyuluhan Tentang Penerapan Terapi Komplemeter Akuepresur dengan Penurunan Mual Muntah pada Ibu Hamil Trimester I di PMB Eka Sri Wahyuni Tahun 2024 - Eka Sylviana Siregar; Maulina Mawaddah; Safinatunnazria Safinatunnazria; Ira Wati Lubis (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
Nausea and vomiting are common complaints experienced by pregnant women, especially in the first trimester of pregnancy. This condition not only causes discomfort, but can also affect the physical and emotional health of pregnant women. This study aims to provide education about the application of complementary acupressure therapy as a non-pharmacological alternative in reducing symptoms of nausea and vomiting in first trimester pregnant women. This counseling will be carried out at PMB Eka Sri Wahyuni ​​in 2024, involving a number of pregnant women who are in their first trimester. The method used is an educational approach through acupressure training which can be applied independently by pregnant women. It is hoped that the results of this activity will increase pregnant women's knowledge about complementary therapies and provide practical solutions that are effective in reducing nausea and vomiting, thereby improving the quality of life during pregnancy.